ANALISA KESELAMATAN DAN KESEHATAN KERJA PADA NELAYAN - Andi Hendrawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2017)
Occupational safety and health is an activity to create a work environment that is safe, comfortable and how to increase the health care workforce and good physical, spiritual and social. Occupational health and safety is specifically intended to prevent or reduce accidents and as a result, and to secure the vessel, equipment, and products of the catch. Survey with cross sectional approach by taking a sample of 30 fishermen, a tool used questionnaires and interviewsBased on the research shows that the level of knowledge about occupational health and safety is obtained as large berpengatahuan less that 23 people or 76.7%, and that knowledge is quite 6 people or 20% were good only 1 of 3.3%, was obtained as a big nutritional status never experienced itching disease that is 18 or 60% and who had cataract diseased 10 or 33.6% were ever have hypertension / diabetes 2 is 6.7%., nutritional status is obtained as large itchy disease never experienced that 18 people or 60% and who had cataract diseased 10 or 33.6% were ever have hypertension / diabetes 2 is 6.7%.